2010
DOI: 10.1007/s10700-010-9088-8
|View full text |Cite
|
Sign up to set email alerts
|

International disaster relief planning with fuzzy credibility

Abstract: As a consequence of more extensive collaboration between countries, the need for better humanitarian relief assistance has become a significant challenge to the international community. In case of a disaster exceeding the national response capacity of the affected country, donor countries provide the relief items, which are then consolidated at collection points to be shipped to points of delivery in the stricken country. After the items are transported to the point of delivery, the responsible authority in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Related to the topics studied in this work, Arora, Raghu, and Vinze (2010) focused on the allocation of medical aid for emergencies considering the coordination between regions, whereas Adıvar and Mert (2010) aimed to coordinate international relief items using fuzzy logic to provide a collectiondistribution plan. Altay (2013) developed a model to allocate response personnel, facilities, supplies and equipment with two alternative objective functions; to minimise deployment time or minimise maximum response time.…”
Section: Resource Management Among Multiple Actorsmentioning
confidence: 99%
“…Related to the topics studied in this work, Arora, Raghu, and Vinze (2010) focused on the allocation of medical aid for emergencies considering the coordination between regions, whereas Adıvar and Mert (2010) aimed to coordinate international relief items using fuzzy logic to provide a collectiondistribution plan. Altay (2013) developed a model to allocate response personnel, facilities, supplies and equipment with two alternative objective functions; to minimise deployment time or minimise maximum response time.…”
Section: Resource Management Among Multiple Actorsmentioning
confidence: 99%
“…When a disaster occurs, aid from donor countries and international organizations is sent to the disaster stricken country. For the effective management of these relief goods Adıvar and Mert [52] and Camacho-Vallejo et al [53] suggested models with the objectives of minimizing total response time for delivering and cost for procurement. Details of all the models discussed above for network design and disaster relief distribution in HSC are given in Table 2.…”
Section: Network Design and Relief Distribution In Humanitarian Supplmentioning
confidence: 99%
“…A multi-mode transportation eet (i.e., ground, marine, and air) made the model more e cient and exible in the real world. Therefore, Barbasoglu [19], Rennemo et al [24], Hu [25], Naja et al [26], Adivar and Mert [27], and Ozdamar [28] followed this issue in separate studies.…”
Section: Related Workmentioning
confidence: 99%